2002
DOI: 10.1103/physrevlett.88.207005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Transition in the Pairing Symmetry of the Electron-Doped CupratesLa2xCex

Abstract: We present measurements of the magnetic penetration depth, lambda(-2)(T), in Pr(2-x)Ce(x)CuO(4-y) and La(2-x)Ce(x)CuO(4-y) films at three Ce doping levels, x, near optimal. Optimal and overdoped films are qualitatively and quantitatively different from underdoped films. For example, lambda(-2)(0) decreases rapidly with underdoping but is roughly constant above optimal doping. Also, lambda(-2)(T) at low T is exponential at optimal and overdoping but is quadratic at underdoping. In light of other studies that su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
57
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(66 citation statements)
references
References 21 publications
9
57
0
Order By: Relevance
“…However, this has been contrasted by tunnelling [12,13] and some other specific heat [14] and penetration depth measurements [15,16,17]. In particular, there may be a crossover from d-wave to s-wave symmetries by changing the doped electron concentration [18,19] or decreasing temperature [20]. Although such a crossover may explain the conflicting experimental results on the pairing symmetry in the electron-doped cuprates, the characteristics of such possible s-wave pairing symmetry has yet to be established.…”
Section: Introductionmentioning
confidence: 82%
“…However, this has been contrasted by tunnelling [12,13] and some other specific heat [14] and penetration depth measurements [15,16,17]. In particular, there may be a crossover from d-wave to s-wave symmetries by changing the doped electron concentration [18,19] or decreasing temperature [20]. Although such a crossover may explain the conflicting experimental results on the pairing symmetry in the electron-doped cuprates, the characteristics of such possible s-wave pairing symmetry has yet to be established.…”
Section: Introductionmentioning
confidence: 82%
“…We also note that throughout the exotics this synergy is consistent with the considerable deviations from a strict T c µ et al 2002). Other data shows nodes for underdoped films together with the absence of nodes for overdoped films of this material, and likewise for the lanthanum analog of this material (Biswas et al 2002, Skinta et al 2002b see also Zheng et al 2002).But instead of characterizing the latter electron-doped cuprate results as "a d to s transition", as in these papers, it is far more straightforward and therefore more reasonable to interpret this as simply a change in the degree of anisotropy within the swave gap form of Eq. (1).…”
mentioning
confidence: 80%
“…Pairing symmetry of electron-doped high-T c cuprate superconductors such as Nd 2−x Ce x CuO 4 and Pr 2−x Ce x CuO 4 is a long standing problem [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17]. Although no consensus has been reached yet, more and more recent experimental results have suggested that the order parameter of electron-doped cuprates is likely to have d x 2 −y 2 -wave pairing symmetry [1,2,3,5,9,10,14,16,17], in close resemblance to that of hole-doped materials.…”
Section: Introductionmentioning
confidence: 99%